Identification and Validation of Microsatellite Markers in Rhododendron campanulatum D. Don through cross transferability - Kumar, Deepak; Meena, Rajendra Kumar; Bhandari, Maneesh Singh; Ginwal, Harish Singh (Indian Forester, 2022)
The genetic diversity maintained by Forest Genetic Resources (FGRs) bestow them the capability for survival, adaptation and evolution in response to the changing climatic conditions. Population genetic studies based on DNA based marker may aid in understanding the actual level of diversity and its distribution within and among the populations, gene flow, allele fixation, structuring etc. that could be wisely used in their conservation and management. Rhododendron campanulatum is a medicinally, horticulturally and ecologically important tree species growing at tree line throughout the Himalayas. In the present study, efforts were carried out to identify simple sequence repeat (SSR) markers in R. campanulatum through cross species amplification. In total, 15 SSR markers developed in R. arboreum (Choudhary et al., 2014) were tested for cross transferability and polymorphism in R. campanulatum. Of these, 12 primer pairs were positively amplified but only 5 (SSR-7, SSR-8, SSR-11, SSR-25 and SSR-29) showed polymorphism across the populations. Mean Polymorphic Information Content (PIC), expected heterozygosity (H ) and observed heterozygosity (H ) of these markers were e o recorded as 0.609, 0.360 and 0.343, respectively. Other measures such as genetic differentiation (F ) and gene flow (N ) were recorded as 0.467 and ST m 0.486, respectively. Population of Valley of Flowers had the highest percentage of polymorphic loci (100.0%). Analysis of molecular variance (AMOVA) revealed about 25% among the populations and 75% within population. The markers identified in the study could be highly useful for detailed population genetic analysis of this species.